2007
DOI: 10.1177/0165025407081461
|View full text |Cite
|
Sign up to set email alerts
|

Children's implicit and explicit ethnic group attitudes, ethnic group identification, and self-esteem

Abstract: An increasing amount of research explores how children distinguish different aspects of ethnic group attitudes. However, little work has focused on how these aspects tie in with other social and psychological processes. In the present study, 112 black and white children aged 5-, 7- and 9-years completed tests of implicit and explicit ethnic group attitudes, racial and ethnic identification, and self-esteem. Whereas all children exhibited coherent identification with ethnicity defined in terms of family ancestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
2
18
0
1
Order By: Relevance
“…Ford (2008) indicated a generational decline in prejudice among young British children as a result of social contact between ethnic groups. Although Ford"s study is based on explicit prejudice which is known to be transformed into subtle forms (e.g., Dovidio & Gaertner, 1986;Pettigrew & Meertens, 1995), recent research in London has shown that White British children"s both explicit and implicit attitudes were positive for Black children (Davis, Leman, & Barrett, 2007). Also, in the current sample, perceived ethnic discrimination was generally low (with a mean of 1.47 on a scale from 1 to 5).…”
Section: Cross-ethnic Friendship Numbers and Qualitymentioning
confidence: 55%
“…Ford (2008) indicated a generational decline in prejudice among young British children as a result of social contact between ethnic groups. Although Ford"s study is based on explicit prejudice which is known to be transformed into subtle forms (e.g., Dovidio & Gaertner, 1986;Pettigrew & Meertens, 1995), recent research in London has shown that White British children"s both explicit and implicit attitudes were positive for Black children (Davis, Leman, & Barrett, 2007). Also, in the current sample, perceived ethnic discrimination was generally low (with a mean of 1.47 on a scale from 1 to 5).…”
Section: Cross-ethnic Friendship Numbers and Qualitymentioning
confidence: 55%
“…He suggests that alternative measures of children's implicit rather than explicit attitudes are therefore required to test between the two theories. However, evidence from recent studies using implicit measures (e.g., Davis, Leman & Barrett, 2007;Dunham, Baron & Banaji, 2006) do not support SIDT, with levels of implicit prejudice either remaining steady after 6-7 years of age or declining rather than increasing after this age. SIDT also has difficulty explaining why, in countries which have experienced inter-ethnic conflict or warfare, extreme negativity can be exhibited towards enemy groups at the age of 2-3 years (Bar-Tal, 1996;Bar-Tal & Teichman, 2005;Povrzanovi?, 1997).…”
Section: Theoretical Accounts Of the Development Of Intergroup Attitumentioning
confidence: 86%
“…These studies have found that SoIS item scores always load onto a single factor (eigenvalues ranging between 2.02 and 3.30; % of variance explained ranging between 40.8 and 80.1) and scale reliably (Cronbach's alpha ranging between .60 and .91, with the sole exception of young white children's racial identifications in the study by Davis et al, 2007, where the reliability was only .41). In addition, the test-retest reliability of the SoIS over an eight week period has been found to be .68 (Barrett, 2007).…”
Section: The Shared Methodology Used By the Studies Reported In This mentioning
confidence: 95%
See 1 more Smart Citation
“…This study will look to see whether such differences are present. The inclusion of implicit and explicit measures of prejudice within this study and a focus upon whether children can self-regulate their explicit prejudice, is aligned with recent theorists approaches (e.g., Chevalier & Blaye, 2009;Davis, Leman, & Barrett, 2007;Dunham, Baron, & Banaji, 2006;Lorsbech & Reimer, 2008, 2011Marcovitch, Boseovski, & Knapp, 2007;Rutland, Cameron, Milne, & McGeorge, 2005) and will allow for an examination of the developmental sequence proposed by Devine (1989), that children first learn stereotypical labels associated with particular social groups (or categories); and it is only later that they develop the cognitive ability and flexibility to evaluate critically such stereotype's validity and acceptability. The advantage of this approach is that it provides a common ground for the use of implicitÁexplicit distinction in this field of research.…”
Section: Introductionmentioning
confidence: 81%